Sternal Leiomyosarcoma: Primary or Secondary - Dayang Corieza Febriany; Hairulfaizi Haron; Muhammad Ishamudddin Ismail; Mohd Ramzisham Abdul Rahman; Mohamed Arif Hameed Sultan (Gazi Universitesi, 2023)
Primary leiomyosarcoma of bone is an extremely rare, aggressive and a diagnostically challenging tumor which occurs mainly in the long bones. Clinically and radiographically, it can mimic other malignancy and its diagnosis is based on histopathology, immunochemistry and electron microscopy findings. It can be perplexing to ascertain whether a biopsy confirmed leiomyosarcoma of bone is primary or secondary in origin. Most of the cases are predominantly secondary from a distant metastasis. The case presented here is an illustration and analysis of this diagnostic problem.